2016
DOI: 10.1155/2016/2384894
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Robot-Guided, Software Based Transperineal MRI/TRUS Fusion Biopsy of the Prostate in a High Risk Population of Previously Biopsy Negative Men

Abstract: Objective. In this study, we compared prostate cancer detection rates between MRI-TRUS fusion targeted and systematic biopsies using a robot-guided, software based transperineal approach. Methods and Patients. 52 patients received a MRIT/TRUS fusion followed by a systematic volume adapted biopsy using the same robot-guided transperineal approach. The primary outcome was the detection rate of clinically significant disease (Gleason grade ≥ 4). Secondary outcomes were detection rate of all cancers, sampling effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 23 publications
1
14
0
4
Order By: Relevance
“…Our findings provide a timely evaluation of the utilization of robotic equipment in the prostate cancer diagnostic pathway that utilizes the clinically superior transperineal route. There has been an increased adoption of this technology in units globally but with minimal reported outcomes [9][10][11]. The detection range of csPCa for all the previous similar studies is 50.0%, 52.7%, and 61% which is in-keeping with our overall detection rate of 51.2%.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Our findings provide a timely evaluation of the utilization of robotic equipment in the prostate cancer diagnostic pathway that utilizes the clinically superior transperineal route. There has been an increased adoption of this technology in units globally but with minimal reported outcomes [9][10][11]. The detection range of csPCa for all the previous similar studies is 50.0%, 52.7%, and 61% which is in-keeping with our overall detection rate of 51.2%.…”
Section: Discussionsupporting
confidence: 84%
“…Our study limitations include the heterogeneous nature of our cohort of men which included those with the previous negative prostate biopsy and men who underwent this diagnostic test for the first time. Our study has a small size; however, with the exception of study by Mischinger et al [11], our data report on a larger series than found in the literature [9,10]. All men underwent the procedure under general anesthesia.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Robot-assisted mpMRI/TRUS fusion biopsy of the prostate (iSRobot Mona LisaTM ® , Biobot Surgical, Singapore, Singapore) was performed as a combined strategy by targeting suspicious lesions followed by SB in the same session. Procedural details were described in previous investigations [11]. Eight different surgeons performed the biopsy procedures that were reviewed for this study.…”
Section: Biopsy Proceduresmentioning
confidence: 99%
“…The patients received no transurethral catheter. The detailed procedure has been described previously 16,17 . We analysed the histopathologic results of all targeted biopsies (B x ) taken from lesions in which cancer was detected, and calculated the diagnostic yield on a per-lesion level and on a per-patient level.…”
Section: -D Modeling Equipment Biopsy Technique and Histological Analysismentioning
confidence: 99%